Enhancing Student-Centered Inquiry-Based Learning through Mobile Educational Applications in Secondary School Classrooms - Ismaul Fitroh; Dwi Oktaviana; Jimoh, Olumide Yusuf (International Forum of Researchers and Lecturers, 2024)
This study explores the potential of mobile educational applications to enhance student-centered inquiry-based learning (IBL) in secondary school classrooms. As traditional, teacher-centered pedagogies fail to adequately engage students in critical thinking and problem-solving, IBL offers a promising alternative that encourages active participation and deeper learning. The research investigates how mobile applications can support IBL by facilitating the inquiry process, such as data collection, hypothesis formulation, and collaboration. Through a quasi-experimental design involving secondary school students, the study compares the effectiveness of traditional teaching methods and mobile-assisted IBL. Results indicate that students using mobile applications showed significant improvements in critical thinking, engagement, and academic performance compared to those taught through traditional methods. Teachers and students both reported high satisfaction with mobile apps, particularly in terms of ease of use and educational value. The findings suggest that integrating mobile technologies into the classroom can create more interactive, accessible, and personalized learning experiences, fostering critical thinking and enhancing student outcomes. However, challenges related to infrastructure, teacher training, and digital literacy must be addressed to fully harness the potential of mobile-assisted inquiry-based learning.